2015
DOI: 10.1111/ane.12370
|View full text |Cite
|
Sign up to set email alerts
|

Disability, quality of life, personality, cognitive and psychological variables associated with fatigue in patients with multiple sclerosis

Abstract: This study indicates that MS-related fatigue shows an impact on physical, cognitive and emotional aspects in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 32 publications
3
37
1
2
Order By: Relevance
“…39 Also, it has been shown that the pressures cause changes in economic status, and struggling with this critical situation affects the QOL of patients with MS. 40 Furthermore, it has been shown that psychological symptoms can affect selfefficacy and perception of self-worth in other patient populations 41 because these symptoms can undermine the person's ability to cope. 42 This situation can reduce the patient's QOL.…”
Section: Discussionmentioning
confidence: 99%
“…39 Also, it has been shown that the pressures cause changes in economic status, and struggling with this critical situation affects the QOL of patients with MS. 40 Furthermore, it has been shown that psychological symptoms can affect selfefficacy and perception of self-worth in other patient populations 41 because these symptoms can undermine the person's ability to cope. 42 This situation can reduce the patient's QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Chronification of MS disease causes experience of fatigue in the greater number of patients during much of the day, which results in impaired physical, psychosocial, and cognitive functioning (Lerdal, Celius, Moum, 2003;Fazli, Shayesteh-Azar 2013;Razazian et al, 2014;Fiest et al, 2016). Another aspect of fatigue is the reduction in motivation to perform activities, together with a loss of interest in activities that require physical activity and effort (Fernández-Muñoz et al, 2015;Kaas, Tóthová, 2015). One reason for patientsʼ disinclination to perform such activities is the variability (fluctuation) of the symptom, as fatigue impedes patients in their completion of activities.…”
Section: Discussionmentioning
confidence: 99%
“…Yorgunluk, MS'li bireylerde en sık rastlanan semptomlardan biridir ve bu sıklık %50-90 arasında değişmektedir (6,8). Yorgunluk yaşayan MS'li bireylerin %50-60'ının günlük aktivitelerinde ve öz bakımlarında yetersizlik yaşadıkları, kendilerini işe yaramaz olarak nitelendirdikleri belirtilmekte ve yorgunluk, disabiliteye neden olan faktörler arasında sıralanmaktadır (10,11,12).…”
Section: Multiple Sklerozda Yorgunluk Ve Isı Duyarlılığıunclassified
“…sistemde miyelin kılıfının etkilendiği ve miyelin kılıfında demiyelinizasyonlar olduğu bilinmektedir (6,7). Bu demiyelinizasyon süreci, ileti hızında değişikliğe veya ileti bloğuna neden olmakta ve başlıca yorgunluk olmak üzere çeşitli semptomlara yol açmaktadır (4,8,9).…”
unclassified